IMPROVEMENT OF HUMAN RESOURCES DEVELOPMENT IN THE CONDITIONS OF INDUSTRIAL AND INNOVATIVE ECONOMY OF THE REPUBLIC OF KAZAKHSTAN - L.T.Baituova, (Academic Journal of Physical and Chemical Sciences, 2019)
In Kazakhstan, modernization is considered as a factor of economic growth to improve the socioeconomic system of the society and improve the welfare of the people. The efficiency of economic development is largely determined by the accumulated and realized in the country human capital. Thus, according to the authors, in modern conditions, knowledge and qualifications are important factors of economic growth and social progress of society. The main wealth of any society is people, so the issue of studying the problems of the effectiveness of using the main productive forces that are realized in modern conditions in the form of human capital is relevant. As we see, in Kazakhstan, along with the above-mentioned types of modernization of steel, political modernization and spiritual modernization are carried out, as a necessary component of modernization of a new type, ensuring the success of the nation